Epidural pneumorrhachis in COVID-19: a rare clinical entity. Issue 5 (3rd September 2021) - Rao, Shiavax J.; Lakra, Pallavi; Chittal, Abhinandan R.; Aughenbaugh, Michael; Haas, Christopher J.
ABSTRACT: Pneumorrhachis is an extremely rare clinical entity, involving air entrapment within the spinal canal. We present a unique case of epidural pneumorrhachis accompanying pneumomediastinum and pneumopericardium, in the setting of COVID-19 infection in a 62-year-old woman. Diagnostic testing was remarkable for elevated inflammatory markers, along with mild transaminitis and hyponatremia. CT scan of the chest revealed extensive patchy ground-glass opacities, with no evidence of pulmonary embolism. Intravenous antibiotics and steroids were initiated for management of advanced multifocal bilateral COVID-19 pneumonia. Her hospital course was complicated by rapidly worsening hypoxia accompanied by worsening inflammatory markers. Repeat chest CT showed worsening multifocal opacities, extensive pneumomediastinum, pneumopericardium, and subcutaneous emphysema extending into the lower neck soft tissues, posterior mediastinum, and supraclavicular regions. Neck CT confirmed diffuse subcutaneous emphysema from the mediastinum extending into the retropharyngeal space, neck, and anterior chest wall. Right-sided epidural air in the spinal canal spanning C6-T1 was also noted. She was evaluated by neurosurgery, continued on antibiotics for the epidural air, and transferred to the ICU for frequent monitoring of respiratory and neurological status, which remained stable. Although pneumorrhachis is an extremely rare clinical manifestation, prompt recognition can lead to appropriate early interventions and improved patient outcomes.